Profil Biomarker Apolipoprotein B dan Lipid terhadap Skor SYNTAX pada Pasien Sindrom Koroner Kronik - Chalik, Muhammad Novran; Sukandi, Erwin; Indrajaya, Taufik; Usnizar, Ferry; Indra, Syamsu; Saleh, Imran; Chodilawati, Rukiah; Irfannuddin, Irfannuddin (Jurnal Penyakit Dalam Indonesia, 2026)
Introduction. Apolipoproteins are structural components of plasma lipoproteins that are involved in lipoprotein metabolism and lipid transport, reflecting the number of circulating atherogenic particles. The degree of coronary artery stenosis can be assessed by calculating the Synergy between PCI with TAXUS/paclitaxel-eluting stent and Cardiac Surgery (SYNTAX) score, which is an angiographic scoring system used to evaluate the complexity of coronary artery lesions. This study aimed to investigate the profile of apolipoprotein B and lipids, as well as their correlation with the SYNTAX score in patients with chronic coronary syndrome. Methods. An observational analytic study with a cross-sectional design was conducted from July to September 2024 in the cardiac catheterization laboratory of the Department of Internal Medicine, Mohammad Hoesin General Hospital, Palembang. A total of 69 samples were obtained using consecutive sampling. Samples that met the inclusion and exclusion criteria were analyzed using SPSS version 22. Data were presented in tables and figures. Data analysis was performed using correlation tests with a significance level of p < 0.05. This study received ethical approval from the Ethics Committee of Dr. Mohammad Hoesin General Hospital, Palembang. Results. Among the 34 analyzed subjects, the mean total cholesterol, LDL cholesterol, and apolipoprotein B levels were 175.88 (SD 36.01) mg/dL, 123.59 (SD 35.54) mg/dL, and 141.41 (SD 25.06) mg/dL, respectively. HDL cholesterol and triglyceride levels were not normally distributed and were therefore expressed as medians (range): 42 (29–80) mg/dL and 89 (40–289) mg/dL, respectively. The mean SYNTAX score was 24.09 (SD 2.69). Overall, 20.59% of subjects had a SYNTAX score Conclusions. Patients with chronic coronary syndrome demonstrated elevated apolipoprotein B levels and high SYNTAX scores. Higher apolipoprotein B levels were independently and positively associated with the SYNTAX score. Further studies are needed to investigate additional factors influencing apolipoprotein B levels, lipid profiles, and the SYNTAX score.